Crise e rearticulação burguesa no Brasil:o libertarianismo na constituição do bloco no poder (2008 - 2022) - Dal Pai, Raphael Almeida (2023)
This research consists of an analysis of the bourgeois rearticulation process in Brazil, taking as a time frame the global crisis of 2007/08 and the role of the libertarianism in this process. Therefore, the thesis defended here is that at the emergence of the Great Recession, during the end of the first decade of the 21st century, the world bourgeoisie and its fractions began a process of organization and construction of a consensus, which had as aim preserving their class interests and the maintenance of its hegemony, as well as intensifying the implementation of the neoliberal program. With this as a premise, the research took as its object the activity of the Ludwig von Mises Brazil Institute (IMB) and its members in the period from 2008 to 2020. Assuming as one of its main objectives the disclosure and dissemination that “free” market- oriented relations would be the only “natural” beacons of human society. In this sense, the IMB throughout the established period sought to organize intellectuals and as to build consensus in a systematic way, with the objective of, from the mobilization of intellectual production of authors and concepts of the so-called Austrian School of Economics on the Great Recession, pointing out as a solution to the crisis the need of intensifying the implementation of the neoliberal program in Brazil. In this midst of rearticulation and bourgeois offensive, the members of the IMB conquered positions in the structure of the State, composing Paulo Guedes’ economic team in the Ministry of Economy of Bolsonaro’s government, electing candidates aligned with their ideals, more importantly, becoming an essential Brazilian bourgeois apparatus working on several fronts in the State and civil society.